PERKEMBANGAN KARAKTER 3 DIMENSI TOKOH MADA DALAM FILM HAJI BACKPACKER BERDASARKAN POLA STRUKTUR NARATIF - Ella Yuliatik; Citra Dewi Utami (TEXTURE : Art and Culture Journal, 2018)
The character of the film is important in conveying the story and needs to give an impression to the audience. Characters are created through character development, which results in the development of character characters to create human-like dimensions. This qualitative descriptive study examines the field of cinema which describes Mada’s character in the film Haji Backpacker (2014) based on the pattern of narrative structure. Data collection techniques are carried out through observation and document study. The data analysis technique uses the Miles and Hubberman analysis models with a narrative approach in the form of descriptive studies reading the meaning of the text in the film. The reading is done by dividing the film into sequences, then identifying the character of Mada in 3 dimensions. The results of this study are that Mada’s character experiences a developmental process that shows a change from bad character to a better character. The type of change is a growth arc, with many causes of change based on others.Key Words : Character development, 3 dimentions, Haji Backpacker